SMARTPHONE SALES INFORMATION SYSTEM DEVELOPMENT USING THE WATERFALL METHOD - Arief Fadillah; Arpan Arpan; Rahmad Budi Utomo (Sean Institute, 2022)
Mobile Sales Information System Development is a sales application for recording sales transaction processes, accessed offline using online, local networks, or computing devices such as PC (personal computer) desktops, laptops, and notebooks. I can do it. smartphone. Previously, the sales process was done manually, so the sales transaction recording process was not well documented and it was difficult to create a report, but by doing this, it is necessary to create an information system. May be resolved. The method applied to the development of mobile sales information system applications is the application of the Waterfall method. A system that analyzes functional and non-functional system requirements, database design, and table requirements in the form of entity relationship diagrams (ERD), logical record structures (LRS), and uses Unified Modeling Language (UML) diagrams. Design coding Process Framework Codeigniter 3, from black box test testing, maintenance to application development. The results of this study are applications for sales applications that support sales transaction processing, data manipulation, and rapid printing or generation of reports for the required time period based on the required month or date.